2022
DOI: 10.3390/md20060396
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Chitosan in Surgical and Post-Surgical Materials

Abstract: The continuous advances in surgical procedures require continuous research regarding materials with surgical applications. Biopolymers are widely studied since they usually provide a biocompatible, biodegradable, and non-toxic material. Among them, chitosan is a promising material for the development of formulations and devices with surgical applications due to its intrinsic bacteriostatic, fungistatic, hemostatic, and analgesic properties. A wide range of products has been manufactured with this polymer, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…[ 22 ] Notably, this achievement was reported for an unmodified biomaterial of known biocompatibility, highlighting the potential use of passive actuation in medical applications. [ 23 ] However, hygroscopic actuation was negatively affected by enhanced crystallinity and molecular orientation, suggesting that the space occupied by some water expelled during stress‐induced crystallization was irreversibly lost. This reduction in the hygroscopic pulling force was particularly significant in the direction of uniaxial stress, suggesting that, similar to the cellulose orientation in plants, the hygroscopic forces in highly oriented chitinous biopolymers dominate in the direction perpendicular to the alignment.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Notably, this achievement was reported for an unmodified biomaterial of known biocompatibility, highlighting the potential use of passive actuation in medical applications. [ 23 ] However, hygroscopic actuation was negatively affected by enhanced crystallinity and molecular orientation, suggesting that the space occupied by some water expelled during stress‐induced crystallization was irreversibly lost. This reduction in the hygroscopic pulling force was particularly significant in the direction of uniaxial stress, suggesting that, similar to the cellulose orientation in plants, the hygroscopic forces in highly oriented chitinous biopolymers dominate in the direction perpendicular to the alignment.…”
Section: Resultsmentioning
confidence: 99%
“…Using CS in textiles provided various functionalities, such as anti-microbial, cosmetic, medical, thermoregulating, ultraviolet-protective, and insect-repellent textiles 10 International Journal of Polymer Science [43]. CS-coated surgical materials are cheap and provide anti-microbial activity, which has tremendously helped surgeries [79]. showed that the lowest molecular weight CS inhibited the microbes readily.…”
Section: Anti-microbial Activity Of Csmentioning
confidence: 99%
“…[88][89][90] As a substantial advantage, chitosan nanofibers have an intrinsic capability to inhibit the scar tissue formation on the surgical site. [32,80] On the other hand, regulated recruitment of myofibroblasts in the defect region is a key factor in complete tissue remodeling and depletion of scar formation. The presence of myofibrob-last cells can be easily detected through the surface expression of alpha-smooth muscle actin (𝛼-SMA).…”
Section: Implantation and Histopathological Evaluationsmentioning
confidence: 99%
“…[27,[29][30][31] On the outer layer of the mesh, chitosan nanofibers are capable to provide a biocompatible substrate to enhance the vasculature, antibacterial properties, implant-tissue integration, and tissue remodeling. [32][33][34] Nonetheless, these predicted merits must be holistically evaluated through further characterizations as well as in vitro and in vivo examinations.…”
Section: Introductionmentioning
confidence: 99%